2016
DOI: 10.2903/j.efsa.2016.4446
|View full text |Cite
|
Sign up to set email alerts
|

Annual post‐market environmental monitoring (PMEM) report on the cultivation of genetically modified maize MON 810 in 2014 from Monsanto Europe S.A.

Abstract: However, as the methodology for insect resistance monitoring remained unchanged compared to previous PMEM reports, the GMO Panel reiterates its previous recommendations for improvement of the insect resistance management plan. The GMO Panel considers that the farmer alert system to report complaints regarding product performance could complement the information obtained from the laboratory bioassays, but encourages the consent holder to provide more information in order to be in a position to appraise its usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Guerrero et al, 2004;Adel-Patient et al, 2011) and the GMO Panel identified no indications of safety concern in the context of the applications assessed (EFSA GMO Panel, 2012, 2016a. 28 Sprayed once with glufosinate-ammonium-based herbicides and twice with glyphosate.…”
Section: Assessment Of Allergenicity Of the Newly Expressed Proteins 30mentioning
confidence: 99%
“…Guerrero et al, 2004;Adel-Patient et al, 2011) and the GMO Panel identified no indications of safety concern in the context of the applications assessed (EFSA GMO Panel, 2012, 2016a. 28 Sprayed once with glufosinate-ammonium-based herbicides and twice with glyphosate.…”
Section: Assessment Of Allergenicity Of the Newly Expressed Proteins 30mentioning
confidence: 99%
“…Consistent with its previous recommendations, the GMO Panel acknowledges that the consent holder has provided further details on the laboratory rearing of corn borers, the reference laboratory strains and the methodology of the bioassays (EFSA GMO Panel, 2016). To evaluate and verify data quality, and to be in a position to fully assess the analysis of the laboratory assays performed with the progeny of the corn borers sampled, the consent holder should provide the raw data in future PMEM reports.…”
Section: Gmo Panel Assessmentmentioning
confidence: 99%
“…However, the GMO Panel notes that efforts have been made to develop a methodological framework to facilitate the use of existing networks in the broader context of environmental monitoring (Centre for Ecology and Hydrology, Perseus et al, 2014;EFSA GMO Panel, 2014b;Smets et al, 2014). The GMO Panel encourages that these efforts are continued by relevant parties (EFSA GMO Panel, 2011b The search strategy 29 used for the literature search was similar to that applied in the search reported in the previous annual PMEM report (for further details see EFSA GMO Panel, 2016).…”
Section: Existing Monitoring Networkmentioning
confidence: 99%
See 2 more Smart Citations